Fragmentaiom operation in left atrium for correction of isolated mitral valve disease - Pukas, K. V.; Leoshko, I. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Aim of investigation is to research possibilities of intraoperative renewal of sinus rhythm by proposed method during mitral valve replacement (MVR). In analyzed group are included 161 patients with isolated mitral valve disease in IV stage who were operated in Institute. In 155 patients underwent MVR and 6 mitral valve`s plasty with operation Labyrinth. Plasty of left atrium (LA) was performed in 119 (79,3%) patients for prevention spread of re-entry waves. Operation of LA’s fragmentation (Maze-3,4) was performed in all cases by radio-frequency method (25–30 watt), and also with ligation and resection of LA`s auricle. Among 161 operated patients 3 patients died on a hospital stage. Renewal of sinus rhythm in group pts with LA’s plasty was in 86,7%, than is higher than in alternative group (64,5% (р<0,05)). MVR with operation Maze allows successfully renew sinus rhythm on a hospital stage and stabilize it well during half-year after operation.